2019
DOI: 10.1096/fj.201801869rrr
|View full text |Cite
|
Sign up to set email alerts
|

AMP‐activated protein kinase regulates glycocalyx impairment and macrophage recruitment in response to low shear stress

Abstract: Low shear stress (LSS) increases degradation of the endothelial glycocalyx, leading to production of endothelial inflammation and atherosclerosis. However, the underlying mechanisms of how LSS diminishes the endothelial glycocalyx remain unclear. We showed that LSS inactivated AMPK, enhanced Na+‐H+ exchanger (NHE)1 activity, and induced glycocalyx degradation. Activation of AMPK prevented LSS‐induced NHE1 activity and endothelial glycocalyx impairment. We further identified hyaluronidase 2 (HYAL2) as a mediato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Indeed, it has been previously shown that a smoking cessation program using varenicline or nicotine replacement therapy for 3 months resulted in a decrease of carbon monoxide (CO), oxidative stress, arterial stiffness, and restored the endothelial glycocalyx [ 45 ]. Physical inactivity induces systemic low shear stress in the body, and it has been demonstrated that AMP-activated protein kinase regulates glycocalyx impairment due to hyaluronan degradation and macrophage recruitment in response to low shear stress in a mice common carotid artery ligation model [ 46 ]. Moreover, the vascular endothelial glycocalyx is perturbed by various unfavorable disease conditions, including dehydration, acute infectious disease [ 47 ], trauma [ 48 ], sepsis [ 49 ], ARDS [ 50 ], preeclampsia [ 51 ], gestational diabetes mellitus [ 52 ], and chronic disease conditions, such as hypertension, diabetes [ 19 , 53 ], chronic kidney disease [ 54 ], atherosclerosis [ [55] , [56] , [57] , [58] , [59] , [60] ], stroke [ 61 , 62 ], dementia [ 63 ], microvascular angina [ 64 ], ACS [ 65 ], and heart failure [ 66 ].…”
Section: Vascular Endothelial Glycocalyxmentioning
confidence: 99%
“…Indeed, it has been previously shown that a smoking cessation program using varenicline or nicotine replacement therapy for 3 months resulted in a decrease of carbon monoxide (CO), oxidative stress, arterial stiffness, and restored the endothelial glycocalyx [ 45 ]. Physical inactivity induces systemic low shear stress in the body, and it has been demonstrated that AMP-activated protein kinase regulates glycocalyx impairment due to hyaluronan degradation and macrophage recruitment in response to low shear stress in a mice common carotid artery ligation model [ 46 ]. Moreover, the vascular endothelial glycocalyx is perturbed by various unfavorable disease conditions, including dehydration, acute infectious disease [ 47 ], trauma [ 48 ], sepsis [ 49 ], ARDS [ 50 ], preeclampsia [ 51 ], gestational diabetes mellitus [ 52 ], and chronic disease conditions, such as hypertension, diabetes [ 19 , 53 ], chronic kidney disease [ 54 ], atherosclerosis [ [55] , [56] , [57] , [58] , [59] , [60] ], stroke [ 61 , 62 ], dementia [ 63 ], microvascular angina [ 64 ], ACS [ 65 ], and heart failure [ 66 ].…”
Section: Vascular Endothelial Glycocalyxmentioning
confidence: 99%
“…The parallel-plate flow chamber (Shanghai Medical Instrument School, Shanghai, China) was performed to impose an LSS on the monolayer of EA.hy 926 cells as previously described by Zhang et al [ 24 ]; the laminar with tiled EA.hy 926 cells were placed on the chamber and obtained an LSS (3 dyn/cm 2 ) in the incubator at 37°C for 30 min. The cells under static without flow were used as control.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, vascular endothelial glycocalyx damage is also caused by a decrease in shear stress, and it is known that vascular endothelial glycocalyx damage is responsible for vulnerable plaque formation in the area of arterial bifurcations and strong flexion. In vivo and in vitro models of decreased shear stress caused vascular endothelial glycocalyx degradation, and plaque formation was strongly induced at the same site 19 .…”
Section: Of 13mentioning
confidence: 98%
“…Increasing glycocalyx damage results in further thinning of the vascular endothelial glycocalyx layer. It is known that the reduction of shear stress also causes thinning of vascular endothelial glycocalyx through the inactivation of AMP-activated protein kinase (AMPK) and the activation of hyaluronidase 2 which induces shedding of hyaluronan and exfoliates vascular endothelial glycocalyx 19 . Syndecan-1 is known as a molecule that regulates shear stress-related signals.…”
Section: Molecular Biological Mechanism Of Vascular Endothelial Glycomentioning
confidence: 99%